The Impact of Internal Integration on External Integration - Elimanova, Madina (2013)
Supply chain management (SCM) emphasises the necessity and advantages of abandoning organisational boundaries, and directs organisations to coordinate, cooperate and integrate intra- and inter-organisational relationships as well as coordination of information, material and financial flows throughout the supply chain (SC). This dissertation is a single case study of “Zerde” a pharmaceuticals wholesaler in Kazakhstan, which aims to explore the impact of Internal Integration (II) on External Integration (EI) from its major elements such as organisational capabilities, information sharing, cross-functional teams and joint planning. Secondary data was obtained from the literature review. Primary data was obtained with qualitative research, which included semi-structured interviews with the staff of the company. Four representatives of the company were interviewed via Skype calls and telephone call, the information obtained was recorded by taking hand-written notes. Three research objectives were addressed on the base of the collected data. The results of the research indicated that the company successfully coordinated and integrated information, material and financial flows within its boundaries. Despite, the company failed to externally integrate with suppliers and customers. Key words: Supply chain integration, internal integration, supplier integration, customer integration